Improving the Ability of Kemuning Village Community to Overcome Stunting through Supplementary Food Provision and Health Checks - Fitria Budi Utami; Nuriyatul Fhatonah; Saru Noliqo Rangkuti; Anni Rohimah (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Kemuning Village, Kresek sub-district, Tangerang has the advantage of adequate community self-sufficiency, starting from its aesthetic location, and many rice fields but its location is not too far from the city center. Although the stunting rate in this village has decreased, the relevant village government is not necessarily complacent by continuing to make preventive efforts, one of which is by accepting this community service team to provide additional food and also health checks. Some people who participated in the health check had blood pressure, blood sugar, cholesterol, and uric acid levels above normal.